How To Change a Rotten Attitude A Manual for Building Virtue and Character in Middle and High School Students - Loehrer, Michael C. ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1998)
This book presents ways in which teachers can build virtue and character in middle and high school students. The text is divided into three parts. In part 1, "Measuring Virtue," ways in which virtue can be restored to education are explored. The chapters examine the problems teachers face, the elements of virtue, how to make virtue operational, and how to measure virtue using an instrument devised specifically for this purpose. Ways to deal with the data that are collected are treated in part 2. This section includes a case study and details how to score the instrument that measures virtue. Some of the dynamics of knowledge and virtue are then presented. The last part focuses on ways to restore broken lives and presents the cycles that many students encounter and how willfulness can be turned to willingness; it presents various ways that students can be prepared for virtuous instruction. These include assessing negative feelings, changing perspective, and nurturing desire. The last chapter lists the eight principles for instilling virtue, such as the principle of exceeding expectations, and how these principles can transform students' lives. (RJM)
Availability: Corwin Press, Inc., 2455 Teller Road, Thousand Oaks, CA 91320 (paper: ISBN-0-8039-6650-4, $27.95; cloth: ISBN-0-8039-6640-0, $67.95).
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Attitude Change; Attitude Measures; Behavior Modification; Behavior Problems; Change Strategies; High School Students; Intermediate Grades; Middle School Students; Middle Schools; Secondary Education; Student Behavior; Student Development; Student Problems; Books; Guides, Non-Classroom.